ACTR-91. NUMERICAL SIMULATIONS OF TTFIELDS DISTRIBUTION IN PATIENT MODELS REVEALS A CONNECTION BETWEEN FIELD INTENSITY AND PATIENT OUTCOME - Urman, Noa (Neuro Oncol, 2017)
Preclinical studies show that the efficacy of TTFields increases with field intensity. However, studies investigating the connection between field distribution and patient outcome have yet to be performed. We have developed a novel technique that enables rapid numerical simulation of TTFields distribution within the heads of patients. We are utilizing this technique to investigate the connection between TTFields distribution and patient outcome in patients treated with TTFields during the EF-14 trial (n=466). To date, n=57 cases have been simulated and field intensity distributions in a tumor bed comprising the Gross Tumor Volume (GTV) and a zone extending 1 cm from the GTV were derived. To account for compliance, field values for each patient were multiplied by their average compliance over the first six months of treatment. To test the hypothesis that patient outcome correlates with field intensities, we defined E95 such that 95% of the tumor bed receives field intensities above this value. The patients were split into two groups E95>1.3V/cm (n=13) and E95<1.3V/cm (n=44). E95=1.3V/cm, is the threshold that yielded the most statistically significant difference in OS between the groups. Demographics of the two groups were similar to the demographics of the entire EF-14 trial population and similar to each other. The median OS and PFS were superior when E95>1.3.V/cm OS (35.8 months vs. 23.0 months, p=0.04, HR=0.43) and PFS (11.5 months vs 8.1 months, p=0.12, HR=0.57). Within the E95>1.3V/cm group, a higher percentage of patients showed clinical benefit (stable disease/ partial response, 100% vs 75% p=0.045). OS in both groups is superior to OS in the EF-14-control-arm (16.0 months, p=0.049), indicating that patients benefited from treatment even when field intensities were lower. These preliminary results suggest that field intensity at the tumor bed correlates with patient outcome. Analysis of the full patient group will further elucidate this connection.